Warunki telekomunikacyjne czynnikiem koniecznym do rozwoju społeczeństwa informacyjnego - Budziewicz-Guźlecka, Agnieszka (Conditions of telecommunications as a factor for development of information society, 2006)
The article presents Polish telecommunication market. The liberalization of Polish telecommunication market is simultaneously premised which hastens its integration. Positive effects of this process can be obtained by the analysis of different countries experiences which have already passed the basic integration phase of telecommunication market. In the first part of the paper conditions of telecommunication in Poland and other countries in Europe are considered. In the second part development’s factors of information society are presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 155-166